The Impact of Hedonic Shopping Value and Shopping Lifestyle on Impulsive Buying Mediated by Positive Emotion among Online Marketplace Users in Pekanbaru - Adelia Dwi Anggita; Henni Noviasari; Sri Wahyuni Wildah; Prima Andreas Siregar (Westscience Press, 2023)
This study examined the influ ence of hedonic shopping value and shopping lifestyle on impulsive buying among online marketplace users in Pekanbaru, Indonesia. The study used path analysis to analyse data from 112 respondents and found that hedonic shopping value had no significant effect on impulsive buying, while shopping lifestyle had a positive and significant relationship with impulsive buying. Additionally, hedonic shopping value had a positive and significant effect on positive emotions. The results suggest that to decrease impulsive buying, it is important to focus on creating a positive shopping experience and consider the shopping lifestyle of consumers.